Periodontal Disease and Treatment Needs among Patients with Diabetes Mellitus Type 2 Attending Talaga Bodas Community Health Center in Bandung City - Agus Susanto; Arina Sarah Amnani Manurung; Aldilla Miranda; Siti Sopiatin (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: Periodontitis has been referred to as the sixth complication of diabetes. A number of studies found a higher prevalence of periodontal disease among diabetes patients than among healthy controls. Objective: The objective of the study was to determine the periodontal status and periodontal treatment needs (TN) of diabetes mellitus Type 2 patients attending Talaga Bodas Community Health Center, Bandung City, Indonesia. Methods: This descriptive study included 30 subjects with diabetes mellitus Type 2. The periodontal tissue status and periodontal TN were determined using the Community Periodontal Index of TN. Data on periodontal status and TN are presented in percentages based on subject, sextant, and duration of diabetes mellitus. Results: Periodontitis (53.3%) was more common than gingivitis (43.3%) among diabetes mellitus Type 2 patients. Scaling and root planing were the treatments most commonly required in the diabetes mellitus patients (n = 21.70%) and sextants (n = 81.65.9%). A longer period of diabetes mellitus was associated with a tendency toward more severe periodontal disease and more complex periodontal TN. Conclusion: The prevalence of periodontitis was higher than gingivitis among patients with diabetes mellitus Type 2. The TN of diabetes mellitus Type 2 patients comprised mostly scaling and root planing